Effect of Bi dopant on morphological and optical properties of ZnO semiconductor films produced by the sol-gel spin coating process - Yildiz, Tulay; Kati, Nida; Yalcin, Kadriye (Walter de Gruyter Gmbh, 2021)
In this study, undoped semiconductor ZnO thin film and Bi-doped ZnO thin films were produced using the sol-gel spin coating method. By changing each parameter of the spin coating method, the best conditions for the formation of the film were determined via the trial and error method. When the appropriate parameter was found, the specified parameter was applied for each film. The structural, superficial, and optical properties of the films produced were characterized via atomic force microscope (AFM), UV-visible spectroscopy, and Fourier transform infrared (FTIR), and the effects of Bi dopant on these properties were investigated. When the morphological properties of the undoped and Bi-doped ZnO films were examined, it was observed that they had a structure in a micro-fiber shape consisting of nanoparticles. When the surface roughness was examined, it was observed that the surface roughness values became larger as the rate of Bi dopant increased. By examining the optical properties of the films, it was determined that they were direct band transition materials and Bi-doped thin films were involved in the semiconductor range. In addition, optical properties changed positively with Bi dopant. Since Bi-doped ZnO thin film has a wide bandgap and good optical properties, it is a material that can be used in optoelectronic applications.
Keywords: Sol-gel spin coating; bismuth; ZnO; morphology; optical properties